CYP2A6*4 allele gene high frequency associated with low-density lipoprotein cholesterol (LDL-C) among Javanese Indonesian smokers - Preiffer Agus Prasojo; Christine Patramurti (Universitas Ahmad Dahlan, 2021)
The CYP2A6 gene, which codes the CYP2A6 enzyme, has known to have ahigh polymorphism. This polymorphism could decrease, increase, or eliminate the CYP2A6 enzyme activity. CYP2A6*4, an inactive allele, decreased the CYP2A6 enzyme activity. One of the CYP2A6 enzyme-specific substrates is nicotine. This inactive allele could decrease nicotine metabolism that causes high nicotine levels in the blood. In addition, it caused the increasing levels of Low-Density Lipoprotein Cholesterol (LDL-C) by expanding the lipolysis process. The purpose of this research was to evaluate the effect of the CYP2A6*4 allele gene on LDL-C levels. Respondents in this study were 31 male Javanese smokers. This research is an analytic observational study with a cross-sectional design. Polymerase chain reaction (PCR) methods use to identification the CYP2A6*4 allele gene. This study shows that a high-frequency CYP2A6*4 alleles gene among the subject was detected, with an allele frequency is 93.55%. Furthermore, this CYP2A6*4 allele gene did not impact LDL-C levels, with the Odd Ratio value was 1.636 (P-Value = 0.737). In conclusion, the CYP2A6*4 allele gene does not significantly affect the LDL-C levels in Javanese Indonesian smokers.